Comparative characteristic of conventional and renewable energy sources in terms of economic efficiency and their environmental damage - Matyushenko, Angelina D.; Zoryna, Tatsiana G. (Journal of the Belarusian State University. Economics, 2023)
In the context of globalisation and increased consumer awareness of environmental issues, the introduction of clean and sustainable installations is an important factor in reducing the negative impact of human activity on the environment. A turning point in this interest in a clean planet is the use of renewable energy sources and their growing share in total electricity consumption. However, it is worth determining the feasibility of using green installations in relation to conventional ones, which can be more environmentally damaging. The purpose of this article is to compare non-renewable and renewable energy sources in terms of economic efficiency and environmental damage.
Keywords: energy; conventional energy sources; renewable energy sources; economic efficiency; environmental damage